2015
DOI: 10.4085/1062-6050-50.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Prevalence of Postconcussion Depression Symptoms in Collegiate Athletes

Abstract: Context: Depression is common after concussion and is associated with functional outcome and quality of life after injury. However, few baseline predictors of postconcussion depressive symptoms (PCDS) have been found.Objective: To describe the prevalence of depressive symptoms in a collegiate athlete sample at baseline and postconcussion, compare these levels of symptoms and change in symptoms with those of a control group with no reported concussions in the past year, and examine the baseline predictors for P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 31 publications
4
106
0
3
Order By: Relevance
“…Age effects were examined statistically in different ways across the studies. Moreover, some studies reporting no age effects sometimes had fairly restricted age ranges 74–77. There were, however, large studies that did not find meaningful age effects 21 78.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age effects were examined statistically in different ways across the studies. Moreover, some studies reporting no age effects sometimes had fairly restricted age ranges 74–77. There were, however, large studies that did not find meaningful age effects 21 78.…”
Section: Resultsmentioning
confidence: 99%
“…There was strong evidence of a relationship between acute or subacute symptom burden and worse clinical outcome, although a few studies have not found this association (box 3).
Preinjury characteristics associated with recovery Younger age: Yes: Chermann81; Field82; Terwilliger83; Covassin84; Majerske85; Pellman86; Zuckerman71 No: Lau87; Hang30; McDevitt88; Nelson21; Asplund89; Chrisman75; Vargas74; Morgan58; Meehan42; Meehan90; Meehan6; McCrea91; Lee70; Baker92; Greenhill93; Nelson78; Corwin48; Preiss-Farzanegan94; Heyer80; Kontos67; Kriz77; Miller56, Ellis95; Gibson96 Female sex: Yes: Baker31; Berz97; Henry29, Kostyun79; Bock49; Zuckerman98; Covassin84; Covassin73; Covassin53; Majerske85; Colvin99; Eisenberg68; Ellis95; Miller56; Preiss-Farzanegan(in adults)94; Heyer80; Zemek57 No: Chermann81; Moor100; Hang30; Nelson21; Mayers101; Asplund89; Black72; Chrisman75; Zuckerman102; Zuckerman103; Vargas74; Terwilliger83; Morgan58; Frommer52; Baker92; McDevitt88; Nelson78; Lax104; Ono105; Preiss-Farzanegan (in children/adolescents)94; Covassin106; Kontos67; Wasserman41; Yang107; Meehan90; Gibson96; Meehan6 Race (non-white): Yes: Vargas74; Kontos
…”
Section: Resultsmentioning
confidence: 99%
“…For example, Kontos et al 29 noted elevated depressive symptoms on a scale within 2 weeks of a concussion in high school and collegiate athletes, but the mean score was well below the threshold generally considered consistent with clinically significant depression. Vargas et al 30 …”
Section: Neuropsychiatric Effects Of Repetitive Concussion and Head-imentioning
confidence: 99%
“…Vargas and colleagues (2015) measured depressive symptoms following concussion in a sample of undergraduate student athletes. They reported that, compared to a baseline measure of depression, depressive symptoms increased in 17 of 85 (20%) concussed athletes and only 2 of 42 (4%) control athletes (Vargas et al, 2015). The rate of depressive symptoms after concussion appears to be associated with the number of concussive impacts (Broshek et al, 2015).…”
Section: Depression and Concussionsmentioning
confidence: 99%
“…However, not every concussive injury results in depressive symptoms or issues in cognition, especially in the long-term (Ponsford et al, 2000(Ponsford et al, , 2012. Interestingly, the severity of injury does not seem to predict long-term PCS (Vargas et al, 2015). It is possible that premorbid factors contribute to PCS susceptibility, making certain individuals more vulnerable than others (Broshek et al, 2015).…”
Section: Individual Differencesmentioning
confidence: 99%